Overexpression of Two New Acyl-CoA:Diacylglycerol Acyltransferase 2-Like Acyl-CoA:Sterol Acyltransferases Enhanced Squalene Accumulation in Aurantiochytrium limacinum - Rau, E-Ming; Bartosova, Zdenka; Kristiansen, Kåre Andre; Aasen, Inga Marie; Bruheim, Per; Ertesvåg, Helga (Frontiers in Microbiology, 2022)
Thraustochytrids are heterotrophic marine eukaryotes known to accumulate large amounts of triacylglycerols, and they also synthesize terpenoids like carotenoids and squalene, which all have an increasing market demand. However, a more extensive knowledge of the lipid metabolism is needed to develop thraustochytrids for profitable biomanufacturing. In this study, two putative type-2 Acyl-CoA:diacylglycerol acyltransferases (DGAT2) genes of Aurantiochytrium sp. T66, T66ASATa and T66ASATb, and their homologs in Aurantiochytrium limacinum SR21, AlASATa and AlASATb, were characterized. In A. limacinum SR21, genomic knockout of AlASATb reduced the amount of the steryl esters of palmitic acid, SE(16:0), and docosahexaenoic acid, SE(22:6). The double mutant of AlASATa and AlASATb produced even less of these stearyl esters. The expression and overexpression of T66ASATb and AlASATb, respectively, enhanced SE(16:0) and SE(22:6) production more significantly than those of T66ASATa and AlASATa. In contrast, these mutations did not significantly change the level of triacylglycerols or other lipid classes. The results suggest that the four genes encoded proteins possessing acyl-CoA:sterol acyltransferase (ASAT) activity synthesizing both SE(16:0) and SE(22:6), but with the contribution from AlASATb and T66ASATb being more important than that of AlASATa and T66ASATa. Furthermore, the expression and overexpression of T66ASATb and AlASATb enhanced squalene accumulation in SR21 by up to 88%. The discovery highlights the functional diversity of DGAT2-like proteins and provides valuable information on steryl ester and squalene synthesis in thraustochytrids, paving the way to enhance squalene production through metabolic engineering.